2014
DOI: 10.2147/ijn.s60874
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of radiotherapy efficacy by miR-200c-loaded gelatinase-stimuli PEG-Pep-PCL nanoparticles in gastric cancer cells

Abstract: Radiotherapy is the main locoregional control modality for many types of unresectable tumors, including gastric cancer. However, many patients fail radiotherapy due to intrinsic radioresistance of cancer cells, which has been found to be strongly associated with cancer stem cell (CSC)-like properties. In this study, we developed a nanoparticle formulation to deliver miR-200c, which is reported to inhibit CSC-like properties, and then evaluated its potential activity as a radiosensitizer. miR-200c nanoparticles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Cui et al[158] synthesized a gelatinase-sensitive polymer nanocarrier that was loaded with miR-200c and acted on gastric cancer cells, and their results indicated that gastric cancer cells were significantly sensitized to radiotherapy. In addition, the expression of CD44 was down-regulated, the number of BGC823 cells (CD44 + ) was decreased, the cell invasion, metastasis, and anti-apoptosis ability were weakened, and the resistance characteristics of CSCs were decreased[158]. Moreover, other NDDSs have been used for targeted therapy of CSCs, such as nano-loaded genes, nano-loaded siRNA[159], and nano-compound both drugs[160].…”
Section: Other Methods For the Treatment Of Cscsmentioning
confidence: 99%
“…Cui et al[158] synthesized a gelatinase-sensitive polymer nanocarrier that was loaded with miR-200c and acted on gastric cancer cells, and their results indicated that gastric cancer cells were significantly sensitized to radiotherapy. In addition, the expression of CD44 was down-regulated, the number of BGC823 cells (CD44 + ) was decreased, the cell invasion, metastasis, and anti-apoptosis ability were weakened, and the resistance characteristics of CSCs were decreased[158]. Moreover, other NDDSs have been used for targeted therapy of CSCs, such as nano-loaded genes, nano-loaded siRNA[159], and nano-compound both drugs[160].…”
Section: Other Methods For the Treatment Of Cscsmentioning
confidence: 99%
“…The 3D cultured model mimics in vivo microenvironment and has numerous different characteristics compared with 2D culture, which is a convenient method to induce CSC-like properties ( Chen et al, 2012 ; Xue et al, 2015b ; Usui et al, 2016 ). The combinatorial effects of epigenetic regulation and ionizing radiation contribute to eliminating CSCs have been reported ( Cui et al, 2014 ; Peitzsch et al, 2016 ; Kwon et al, 2017 ). MiRNAs showed differential expression profiles between 2D and 3D cells, and miR-29b-3p had the most dramatic negative change in cells of 3D compared with 2D cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Cell apoptosis was detected using Annexin V-fluorescein isothiocyanate (FITC)/propidium iodide (PI) apoptosis detection kit (Sigma) via flow cytometry. MKN-45 and AGS cells (2x10 5 ) were seeded into 6-well plates, treated with radiation of 6 Gy21 and cultured for 48 hrs. Each group was prepared in triplicate.…”
Section: Methodsmentioning
confidence: 99%